Method for producing carbon dioxide reducing photocatalyst particles

By simplifying the treatment of gallium oxide and silver supply sources, using ultrasonic waves to reduce silver oxides and forming silver dyes through chromium chloride treatment, the problem of difficulty in controlling silver nanoparticles load and particle size in the prior art is solved, and a carbonate reduction photocatalyst with high CO selectivity and high catalytic performance is achieved.

JP7659262B2Active Publication Date: 2025-04-09SUMITOMO METAL MINING CO LTD +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021037386
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-09
Publication Date
2025-04-09
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

The prior art is difficult to improve the loading and particle size control of silver (Ag) as a co-catalyst in the photocatalyst without losing catalytic activity, especially when producing carbonate reduction photocatalysts, where CO selectivity is insufficient.

Method used

By simplifying the treatment of gallium oxide particles and silver supply sources, ultrasonic waves are used to reduce silver oxides, forming metal silver nanoparticles, and forming silver dyes through chromium chloride treatment, improving the dispersion and loading of silver nanoparticles, while controlling their particle size between 10.0 and 50.0 nanometers.

Benefits of technology

High CO selectivity is achieved, the catalytic performance of carbonate reduction photocatalysts is improved, and the high dispersion and loading of silver nanoparticles are ensured, while the loss of catalytic activity caused by particle size growth is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659262000010
    Figure 0007659262000010
  • Figure 0007659262000011
    Figure 0007659262000011
  • Figure 0007659262000012
    Figure 0007659262000012
Patent Text Reader

Abstract

To provide a method for producing a photocatalyst particle for carbon dioxide reduction having improved CO selectivity.SOLUTION: A method for producing a photocatalyst particle for carbon dioxide reduction includes the steps of: preparing gallium oxide (Ga2O3) particles and a silver (Ag) source; adding the gallium oxide particles and the silver source to a reduction liquid to make a reaction liquid; irradiating the reaction liquid with ultrasound to make metal silver-supporting gallium oxide particles; and subjecting the metal silver-supporting gallium oxide particles to chromium (Cr) treatment, to make gallium oxide particles supporting silver (Ag) nanoparticles and silver chromate (Ag2CrO4) nanoparticles.SELECTED DRAWING: Figure 5
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing carbon dioxide reducing photocatalyst particles. [Background technology]

[0002] Water splitting and carbon dioxide reduction technology using semiconductor photocatalyst particles has attracted attention as a technology that can solve energy and environmental problems. By supporting nanoparticles made of silver (Ag) or the like as co-catalysts on these photocatalyst particles, it is expected that the effect of trapping electrons generated by photoexcitation and promoting charge separation and the effect of selecting carbon dioxide reduction products can be achieved. For example, with a normal photocatalyst, water is split into hydrogen (H2) and oxygen (O2) when irradiated with light. In contrast, with a photocatalyst supporting silver particles, carbon monoxide (CO) is generated together with hydrogen (H2) through the reduction of carbon dioxide (CO2). Gallium oxide particles supporting silver nanoparticles as co-catalysts (gallium oxide particles supporting silver nanoparticles) are known as such carbon dioxide reduction photocatalysts.

[0003] Carbon monoxide (CO) is an important starting material in the chemical and industrial industries, and can be reacted with hydrogen to synthesize various fuels and chemicals. Therefore, in a carbon dioxide reduction photocatalyst, it is desirable to have a high carbon monoxide production rate, i.e., a high CO selectivity. Here, CO selectivity is the ratio of the carbon monoxide (CO) gas generation rate to the total of the hydrogen (H2) gas generation rate (amount) and the carbon monoxide (CO) gas generation rate generated by the reduction reaction, as expressed in the following formula (1).

[0004]

number

[0005] Meanwhile, methods such as impregnation and photoelectrodeposition (photoelectrodeposition) have been known as methods for supporting metal nanoparticles. For example, Patent Document 1 describes, with regard to a method for reducing carbon dioxide, that CO2, H2O, and a photocatalyst are irradiated with light to generate CO2 by a reaction that reduces CO2, that a catalyst in which silver is supported on gallium oxide is used in the photoelectrodeposition or impregnation method, that in the photoelectrodeposition method, gallium oxide powder is added to an alcoholic aqueous solution containing a silver precursor such as silver nitrate, and then light is irradiated to reduce the silver precursor, and that in the impregnation method, gallium oxide is added to an aqueous silver precursor solution, stirred, water is removed, and then the solution is heated and dried, and further calcined in air (claims 1, 2, and

[0015] of Patent Document 1).

[0006] Furthermore, although not related to carbon dioxide reduction catalysts, Patent Document 2 discloses a method for producing a precious metal nanomaterial, which comprises the steps of irradiating ultrasonic waves to disperse one or more types of precious metal oxide in a solvent to obtain a precious metal oxide dispersion, and heating the precious metal oxide dispersion. It describes how the solvent further contains a carrier for supporting the precious metal, and how it is possible to obtain a precious metal nanomaterial supported with a high degree of dispersibility on the surface of the carrier, which can be suitably used as a catalyst for fuel cells, a catalyst for material synthesis, etc. (Claims 1, 6, and

[0014] of Patent Document 2). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2012-192302 A [Patent Document 2] JP 2008-24968 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, the inventors have found that the photocatalysts supported with silver by the impregnation method or photoelectrodeposition method proposed in Patent Document 1 have a certain effect but have room for improvement. That is, in order to fully exert the effect of the co-catalyst silver (Ag), it is desirable to increase the amount of silver supported to a certain extent. In addition, it is desirable for the particle size of silver to be small, on the order of several tens of nm. This is because catalytic activity is lost if the particle size is too large. However, with photocatalyst particles produced by the impregnation method or photoelectrodeposition method, there is a problem that the silver particles aggregate and the particle size becomes large when the silver concentration (supported amount) is increased. Therefore, it is difficult to support a large amount of silver nanoparticles with a small particle size.

[0009] Patent Document 2 does not intend to use precious metal nanomaterials as carbon dioxide reduction photocatalysts, much less to reduce the particle size of nanomaterials to the order of several tens of nm. In fact, in the examples of Patent Document 2, it merely teaches that precious metal (Pt) nanoparticle-supported spherical carbon and precious metal (Pt) nanotubes are prepared, and that they are suitable for use as catalysts for fuel cells, catalysts for material synthesis, medical and food additives, and conductive pastes (

[0043] to

[0062] of Patent Document 2).

[0010] On the other hand, when synthesizing metal nanoparticles, a method is known in which the raw material concentration is reduced and a large amount of organic protective agent is used to synthesize uniform and fine particles. However, when photocatalyst particles are produced using this method, there are problems in that the yield of photocatalyst particles is low and the organic protective agent adheres to the particle surface. Since the attached organic protective agent reduces the catalytic activity, the catalyst particles must be calcined at high temperatures to decompose and remove it. In catalyst particles that have been calcined in this way, the particle size of the metal nanoparticles becomes large. Therefore, it is difficult to highly disperse and support fine silver nanoparticles in a large amount using conventional methods, and there are limitations in efficiently producing photocatalyst particles with excellent catalytic performance, especially CO selectivity.

[0011] The present inventors have conducted studies in light of such conventional problems, and have discovered that a photocatalyst with improved CO selectivity can be obtained by a simple method of irradiating gallium oxide particles and a silver source with ultrasonic waves to precipitate silver nanoparticles as a promoter with high dispersion and high loading, and by further performing a chromium (Cr) treatment.

[0012] The present invention was completed based on these findings, and an object of the present invention is to provide a method for producing carbon dioxide-reducing photocatalyst particles having improved CO selectivity. [Means for solving the problem]

[0013] The present invention includes the following aspects (1) to (12). In this specification, the expression "to" includes both ends of the expression. In other words, "X to Y" is synonymous with "X or more and Y or less."

[0014] (1) providing gallium oxide (Ga2O3) particles and a silver (Ag) source; adding the gallium oxide particles and the silver source to a reduction solution to prepare a reaction solution; A step of irradiating the reaction solution with ultrasonic waves to produce metallic silver-supported gallium oxide particles; and A method for producing carbon dioxide reducing photocatalyst particles, comprising a step of subjecting the metallic silver-supported gallium oxide particles to a chromium (Cr) treatment, thereby producing gallium oxide particles supporting metallic silver (Ag) nanoparticles and silver chromate (Ag2CrO4) nanoparticles.

[0015] (2) The method according to (1) above, wherein the silver (Ag) source comprises silver oxide (AgO).

[0016] (3) The method according to (1) or (2) above, wherein the reducing solution contains an alcohol.

[0017] (4) The method according to any one of (1) to (3) above, wherein the ultrasonic wave has a frequency of 28 to 45 kHz.

[0018] (5) Any of the above methods (1) to (4), wherein the ultrasonic irradiation is carried out for 1 to 10 hours.

[0019] (6) Any of the above methods (1) to (5), in which the metallic silver-supporting gallium oxide particles before the chromium treatment are subjected to a heat treatment at a temperature of 100° C. or higher in an oxygen-containing atmosphere.

[0020] (7) Any of the above methods (1) to (6), in which, when carrying out the chromium treatment, the gallium oxide particles supported on metallic silver are immersed in an aqueous solution in which a chromium (Cr) compound is dissolved to precipitate the chromium (Cr) compound on the surface of the gallium oxide particles supported on metallic silver, and then the gallium oxide particles supported on metallic silver with the chromium (Cr) compound precipitated thereon are subjected to a heat treatment.

[0021] (8) The method according to (7) above, wherein the heat treatment is carried out at a temperature of 400 to 700° C. for 1 to 10 hours.

[0022] (9) The method according to any one of (1) to (8) above, wherein the metallic silver (Ag) nanoparticles have an average particle size of 10.0 to 50.0 nm.

[0023] (10) The method according to any one of (1) to (9) above, wherein the average particle size of the silver chromate (Ag2CrO4) nanoparticles is 1.0 to 30.0 nm.

[0024] (11) The method according to any one of (1) to (10) above, wherein the amount of the supported silver component is 0.3 to 10.0% by mass, calculated as metallic silver, based on the mass of the gallium oxide particles.

[0025] (12) The method according to any one of (1) to (11) above, wherein in a CO2 reduction photocatalyst performance evaluation test, the CO selectivity of the photocatalyst particles is 30% or more. Effect of the Invention

[0026] According to the present invention, there is provided a method for producing carbon dioxide reducing photocatalyst particles having improved CO selectivity. [Brief description of the drawings]

[0027] [Figure 1] 1 shows the mechanism of silver nanoparticle loading. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing an example of an evaluation device. [Diagram 3] The mechanism of photocatalytic reaction is shown. [Figure 4] 1 shows XRD patterns of the example and comparative sample. [Diagram 5] 1 shows a STEM photograph of an example sample. [Figure 6] 4 shows a STEM photograph of a comparative sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] A specific embodiment of the present invention (hereinafter, referred to as the present embodiment) will be described below. However, the present invention is not limited to the following embodiment, and various modifications are possible within the scope of the present invention.

[0029] <<1. Method of manufacturing photocatalyst particles>> The method for producing the carbon dioxide reduction photocatalyst particles (hereinafter, sometimes collectively referred to as "photocatalyst") of this embodiment includes the following steps: a step of preparing gallium oxide (Ga2O3) particles and a silver (Ag) supply source (preparation step), a step of adding the prepared gallium oxide particles and the silver supply source to a reduction solution to prepare a reaction solution (mixing step), a step of irradiating the obtained reaction solution with ultrasound to prepare metallic silver-supported gallium oxide particles (ultrasonic treatment step), and a step of performing chromium (Cr) treatment on the obtained metallic silver-supported gallium oxide particles, thereby preparing gallium oxide particles carrying metallic silver (Ag) nanoparticles and silver chromate (Ag2CrO4) nanoparticles (Cr treatment step). Details of each step are described below.

[0030] <Preparation process> In the preparation step, gallium oxide (Ga2O3) particles and a silver (Ag) supply source are prepared. The gallium oxide (Ga2O3) particles are not particularly limited as long as they are used in photocatalysis. Ga2O3 is known to be of α-type, β-type, γ-type, δ-type, and ε-type, and any of them may be used. However, β-type (β-Ga2O3), which is a stable oxide, is preferable. The size of the particles is also not particularly limited. For example, the average particle diameter of the particles is 0.3 to 5.0 μm. Furthermore, the shape of the particles is also not particularly limited. For example, spherical, irregular, and anisotropic shapes (rod or plate-like, etc.) can be mentioned. When the particles are rod-like, for example, those with a major axis diameter of 1.0 to 5.0 μm and a minor axis diameter of 0.3 to 1.0 μm can be used.

[0031] The silver (Ag) supply source is not limited as long as it can supply silver. Specific examples include oxides, inorganic metal salts, and / or organic metal compounds. Examples of inorganic metal salts include nitrates, chlorides, and / or sulfates. The silver supply source may be soluble in the reducing solution, or may not be soluble in the reducing solution. A preferred silver supply source includes silver oxide. Silver oxide is composed only of silver ions and oxygen ions, so it is easy to handle and does not have problems such as waste disposal. As silver oxide, Ag2O, AgO, and Ag2O3, which have different oxidation numbers of silver, are known, and any of them can be used. However, Ag2O, which is more easily available, is preferred. The size of the silver supply source is also not particularly limited. For example, the average particle size of the silver supply source is 0.3 to 3.0 μm.

[0032] <Mixing process> In the mixing step, the prepared gallium oxide particles and silver source are added to the reduction solution to prepare a reaction solution. The mixing ratio of the gallium oxide particles and the silver source can be adjusted so that the amount of silver carried in the final photocatalyst is the desired value. If the amount of silver carried is too small, it becomes difficult to fully utilize the effect of the co-catalyst. As a result, the CO gas generation rate and CO selectivity are low when the photocatalyst is used for CO2 reduction. On the other hand, if the amount of silver carried is too high, the CO gas generation rate decreases.

[0033] The reducing liquid is not limited as long as it is a liquid having reducing properties. It may be a liquid having reducing properties by itself, or may be a liquid having no reducing properties in which a reducing agent is dissolved. However, it is preferable that the reducing liquid is a liquid having reducing properties by itself. It is also not necessary to contain a separate reducing agent. As such a reducing liquid, alcohols such as ethanol and propanol, which are less toxic and easily available, are preferable. A mixed liquid of alcohols and water can also be used. However, when using a mixed liquid, if the water content is excessively high, it becomes difficult to exert a sufficient reducing effect. Therefore, the water content in the reducing liquid is preferably 50% by volume or less, more preferably 25% by volume or less. The lower limit of the water content is not particularly limited, and may be 0% by volume.

[0034] <Ultrasonic treatment process> In the ultrasonic treatment step, the reaction solution is irradiated with ultrasonic waves to produce gallium oxide particles carrying metallic silver nanoparticles. During this process, the surface of the silver source in the reaction solution is ultrasonically reduced to become metallic silver (Ag) nanoparticles, which are then carried on the surface of the gallium oxide particles. The gallium oxide particles carrying metallic silver nanoparticles become photocatalyst particles.

[0035] The mechanism of metallic silver nanoparticle support is explained using Figure 1. When ultrasonic waves are irradiated, compression waves are generated in the reaction solution, which generates repeated positive and negative pressures. During negative pressure cycles, countless fine bubbles are generated in the reaction solution due to evaporation. During positive pressure cycles, these bubbles collapse and give a strong impact force to the surroundings. This phenomenon is called ultrasonic cavitation. Cavitation uniformly disperses the gallium oxide particles and silver source in the reaction solution and cleans their surfaces. Cavitation also generates tiny hot spots with high temperature and pressure. The generated hot spots decompose and reduce the silver source, and also act on the reaction solution to generate radicals, which promote the decomposition and reduction of the silver source. In this way, metallic silver nanoparticles are generated from the silver source.

[0036] For example, when solid silver oxide (Ag2O) is used as the silver supply source, hot spots and radicals act on the silver oxide, and the silver oxide is decomposed and reduced on the surface, resulting in the precipitation of silver nanoparticles. The silver nanoparticles grow gradually, and when they grow to a certain extent, the interfacial stress between the silver oxide and the silver nanoparticles becomes a limit and they are detached. Alternatively, an intermediate product is generated from the silver oxide by the action of ultrasound, and hot spots and radicals act on this intermediate product to generate silver nanoparticles in the reaction solution. The detached or generated silver nanoparticles move to the surface of the gallium oxide particles by the physical action of ultrasound and are adsorbed there. In this way, gallium oxide particles carrying silver nanoparticles are obtained. The silver nanoparticles generated by ultrasonic reduction are minute. In addition, since no organic protective agent or high-temperature firing is required, it is possible to produce gallium oxide particles (photocatalyst particles) carrying fine silver nanoparticles.

[0037] If the photocatalyst particles contain a silver source other than silver nanoparticles, it may be difficult to fully exert the effect of the co-catalyst. In this regard, by using ultrasonic treatment, it is possible to obtain photocatalyst particles that contain almost no silver source (silver oxide, etc.). For example, it is possible to obtain photocatalyst particles in which no peak of silver oxide (Ag2O) is observed in the X-ray diffraction pattern.

[0038] There is no need to use a special device for the ultrasonic treatment, and a device equipped with a normal ultrasonic oscillation source may be used. For example, a commercially available ultrasonic cleaner may be used. The treatment may be performed under normal conditions. For example, the frequency of the ultrasonic waves may be 20 to 100 kHz, or 28 to 45 kHz. The ultrasonic treatment may be performed continuously at the same frequency, or the frequency may be switched during the treatment using a frequency oscillation switching mode. The frequency may be switched once or multiple times. By performing the treatment in a frequency oscillation switching mode (for example, a two-frequency switching oscillation mode of 28 kHz / 45 kHz), it is possible to further improve the dispersibility of the gallium oxide particles in the liquid. In addition, the output of the ultrasonic waves may be 10 to 500 W, or 50 to 200 W. Furthermore, the treatment time may be 1 to 10 hours. By extending the treatment time, it is possible to convert all of the silver source into silver nanoparticles and support them on the gallium oxide particles. On the other hand, by shortening the treatment time, it is possible to adjust the amount of silver nanoparticles supported.

[0039] The product obtained by ultrasonic treatment (gallium oxide particles carrying metallic silver nanoparticles) exists in a dispersed or precipitated state in the reaction solution. Therefore, the product is recovered from the reaction solution and dried. For recovery, known separation means such as filtration or centrifugation may be used. Drying may be performed under conditions that do not cause excessive particle growth of the silver nanoparticles, for example, at 100°C or less.

[0040] <Heat treatment process> If necessary, the gallium oxide particles carrying metallic silver nanoparticles may be heat-treated at a temperature of 100°C or higher in an oxygen-containing atmosphere before the Cr treatment described below is performed. Heat treatment of the silver-loaded gallium oxide particles produced by the ultrasonic loading method can remove organic matter derived from ethanol remaining on the particle surface and can further reduce the particle size of the silver (Ag) nanoparticles. This heat treatment action allows more selective generation of CO when used as a CO2 reduction photocatalyst.

[0041] The heat treatment is preferably carried out at 100°C or higher in an atmosphere containing oxygen. It is not necessary to use a special apparatus for the heat treatment, and a general electric furnace capable of firing in the air can be used. At temperatures below 100°C, the decomposition of organic substances and the influence on the particle size of silver (Ag) nanoparticles are small, and the effect cannot be expected.

[0042] <Cr treatment step> In the Cr treatment step, silver chromate (Ag2CrO4) is formed on the gallium oxide particles supporting the metallic silver nanoparticles. Thereby, gallium oxide particles supporting metallic silver (Ag) nanoparticles and silver chromate (Ag2CrO4) nanoparticles can be obtained.

[0043] As long as metallic silver nanoparticles and silver chromate nanoparticles can be supported, the Cr treatment method is not limited. However, it is preferably carried out according to the following procedure. That is, the gallium oxide particles supporting metallic silver are immersed and dried in an aqueous solution in which a chromium (Cr) compound is dissolved to deposit the chromium (Cr) compound on the surface of the gallium oxide particles supporting metallic silver. As the chromium compound, water-soluble compounds such as chromium(III) nitrate, chromium sulfate hydrate, and chromium chloride hydrate may be used. Thereafter, the gallium oxide particles supporting metallic silver on which the chromium (Cr) compound has been deposited are subjected to a heat treatment. As a result, silver (Ag) and chromium (Cr) react to form silver chromate (Ag2CrO4). The heat treatment may be carried out, for example, at a temperature of 400 to 700°C for 1 to 10 hours.

[0044] <<2. Photocatalyst particles>> The carbon dioxide reduction photocatalyst particles of this embodiment include gallium oxide (Ga2O3) particles, metallic silver (Ag) nanoparticles and silver chromate (Ag2CrO4) nanoparticles supported on the surface of the gallium oxide particles. In these photocatalyst particles, the Ag nanoparticles and the Ag2CrO4 nanoparticles are supported in a dispersed state on the surface of the Ga2O3 particles. Thereby, the photocatalytic performance of the photocatalyst particles becomes excellent.

[0045] Gallium oxide (Ga2O3) particles function as a main catalyst, and are not particularly limited as long as they are used as photocatalysts. Ga2O3 is known to be of α-type, β-type, γ-type, δ-type, and ε-type, and any of them may be used. However, β-type (β-Ga2O3), which is a stable oxide, is preferable. The size of the particles is also not particularly limited. For example, the average particle diameter of the particles is 0.3 to 5.0 μm. Furthermore, the shape of the particles is also not particularly limited. For example, spherical, irregular, and anisotropic shapes (rod or plate-like, etc.) can be mentioned. When the particles are rod-like, for example, those with a major axis diameter of 1.0 to 5.0 μm and a minor axis diameter of 0.3 to 1.0 μm can be used.

[0046] Metallic silver (Ag) nanoparticles function as co-catalysts, and their average particle size is on the order of nm. By making metallic silver nanoparticles finer, the catalytic performance of the photocatalyst is improved. On the other hand, if silver nanoparticles are larger than the order of nm, there is a risk that they will lose their co-catalyst functions, such as catalytic activity, or that the surface active sites of the gallium oxide particles will decrease.

[0047] The average particle diameter of the metallic silver (Ag) nanoparticles is preferably 10.0 to 50.0 nm. By setting the average particle diameter to 10.0 nm or more, it is possible to form silver nanoparticles without the need to lower the Ag concentration (loading amount) or add an organic surface protective agent. On the other hand, by setting the average particle diameter to 50.0 nm or less, it is possible to prevent problems such as loss of function as a cocatalyst, such as catalytic activity, and reduction in the number of surface active sites of gallium oxide particles. The average particle diameter is more preferably 10.0 to 30.0 nm. The average particle diameter can be determined by observing the photocatalyst particles using a transmission electron microscope (TEM). As an example, a method is given in which the particle size distribution of the silver nanoparticles is determined visually or by image analysis software, and the average value is calculated from this particle size distribution.

[0048] Silver chromate (Ag2CrO4) nanoparticles assist the function of the co-catalyst of metallic silver nanoparticles. In other words, chromium (Cr) ions generated from silver chromate react with carbon dioxide (CO2) to form carbonate when acting as a catalyst. Therefore, by providing photocatalyst particles with silver chromate nanoparticles, carbonate and the carbonate ions generated from it can be placed in the vicinity of the co-catalyst silver nanoparticles, which results in the effective promotion of carbon dioxide reduction. Ag2CrO4 nanoparticles can be produced by mixing metallic silver-supported Ga2O3 particles with an aqueous solution of chromium (III) nitrate and then heat-treating the mixture.

[0049] The average particle diameter of silver chromate (Ag2CrO4) nanoparticles is preferably 1.0 to 30.0 nm. By making the average particle diameter 1.0 nm or more, there is an effect that the particles can be stably supported without aggregation. On the other hand, by making the average particle diameter 30.0 nm or less, there is an effect that the catalytic performance can be improved by increasing the number of active sites. The average particle diameter is more preferably 1.0 to 20.0 nm. The average particle diameter of silver chromate nanoparticles may be measured by the same method as that of metallic silver nanoparticles.

[0050] The amount of the silver (Ag) component supported is preferably 0.3 to 10.0% by mass relative to the gallium oxide (Ga2O3) particles in terms of metallic silver. Here, the amount of the silver component supported is the total amount of silver (Ag) contained in each of the metallic silver nanoparticles and the silver chromate nanoparticles. If the amount supported is too small, it becomes difficult to fully exert the effect of the co-catalyst. Therefore, when a photocatalyst is used for CO2 reduction, the CO gas generation rate and the CO selectivity become low. On the other hand, if the amount supported is too large, the CO gas generation rate decreases. The amount supported can be adjusted by controlling the blending amount of the silver source and the ultrasonic treatment conditions. The amount of the silver nanoparticles supported may be 0.5% by mass or more, 1.0% by mass or more, 3.0% by mass or more, or 5.0% by mass or more. The amount supported may be 7.5% by mass or less, 5.0% by mass or less, 3.0% by mass or less, or 1.0% by mass or less.

[0051] The photocatalyst particles of this embodiment have excellent catalytic performance, particularly CO selectivity. For example, in a CO2 reduction photocatalyst performance evaluation test, the CO selectivity is 30% or more. This makes it possible to increase the proportion of CO gas generated by CO2 reduction. The CO selectivity may be 40% or more, 50% or more, 60% or more, or 70% or more. The upper limit of the CO selectivity is not particularly limited, but is typically 90% or less, more typically 80% or less.

[0052] The CO2 reduction photocatalytic performance evaluation test may be performed using a known evaluation device. An example of the evaluation device is shown in FIG. 2. The evaluation device (2) is composed of a tank (4) and a high-pressure mercury (Hg) lamp (6) installed inside the tank (4). The tank (4) is filled with an evaluation solution (22). The tank (4) is also equipped with a gas inlet pipe (8), a gas outlet pipe (10), a pH meter (12), a rubber stopper (14), and a stirrer (16). A bubbling filter (18) is installed at the tip of the gas inlet pipe (8). The mercury lamp (6) is cooled by cooling water (20) flowing around it.

[0053] The evaluation test may be performed as follows. Pure water, sodium bicarbonate (NaHCO3), and a sample (photocatalyst particles) are mixed to prepare an evaluation solution (22). This evaluation solution (22) is placed in a tank (4) of an evaluation device (2) and stirred with a stirrer (16). Carbon dioxide (CO2) gas (30) is blown in through a gas inlet pipe (8), and at the same time, UV light from a high-pressure mercury lamp (6) is irradiated onto the evaluation solution (22). After irradiation for a predetermined time, the generated gas (32) is introduced through a gas outlet pipe (10) into a gas chromatograph (34) and analyzed there. The generation rates (amounts) of hydrogen (H2), oxygen (O2), and carbon monoxide (CO) are determined by this analysis. The obtained generation rates are used to calculate the CO selectivity based on the following formula (1).

[0054]

number

[0055] It is expected that the particle size and electronic transition state of silver nanoparticles will affect the catalytic performance of the photocatalyst, for example, the CO selectivity. This will be explained based on the mechanism of CO2 reduction by gallium oxide particles carrying metallic silver nanoparticles (photocatalyst particles) (Figure 3). As shown in Figure 3, when light with energy hν is irradiated onto the particles, electrons (e - ) and holes (h + In this process, the metallic silver nanoparticles (promoter) separate charges (electrons e - and hole h + The separation of holes (h + ) reacts with the surrounding water (HO), and the reaction shown in the following formula (2) proceeds to the right, producing oxygen (O2) and protons (H + ) is produced. On the other hand, electrons (e - ) is converted into carbon dioxide (CO2) and protons (H + ), the reactions shown in the following formulas (3) and (4) proceed to the right, producing carbon monoxide (CO), water (H2O), and hydrogen (H2). In principle, the reaction shown in the following formula (5) proceeds when the reactions in the following formulas (2) to (4) are combined.

[0056]

number

number

number

number

[0057] When the reactions of the above formulas (3) and (4) occur to the same extent, the CO selectivity (CO generation rate / (H2 generation rate+CO generation rate)) is constant as shown in the above formula (5). However, in reality, these reactions do not necessarily occur to the same extent. When the reaction of the above formula (3) occurs preferentially, the CO selectivity increases.

[0058] In the reaction of the above formula (3), it has been reported that carbon dioxide (CO2) is adsorbed on the catalyst surface as a carbonate species, and is converted to a formate species, which is a reaction intermediate, by irradiation with light, and then interacts with water molecules to become carbon monoxide (CO). This report also suggests that the silver co-catalyst promotes the generation of reaction intermediates. Therefore, it is expected that the reaction of the above formula (3) will occur preferentially and the CO selectivity will be further improved by enhancing the action of charge separation and the action of reaction intermediate generation by the metallic silver nanoparticles (co-catalyst). In this regard, it is speculated that the photocatalyst particles of this embodiment have fine supported silver nanoparticles with a unique electronic transition state, and therefore these act in a combined manner to enhance the action of charge separation and the action of reaction intermediate generation.

[0059] By adopting such a manufacturing method, it is possible to easily obtain catalyst particles with excellent catalytic performance, especially CO selectivity. Although the detailed reason is unclear, it is speculated that this is because the supported silver nanoparticles generated by ultrasonic reduction are fine and have a unique electronic transition state. In other words, the silver nanoparticles (co-catalyst) generated by ultrasonic reduction treatment have a small particle size. It is also considered that the unique electronic transition state is caused by the action of high-temperature and high-pressure hot spots and radicals generated during ultrasonic treatment. In fact, it has been reported that the hot spots generated by ultrasonic treatment are as high as nearly 5000°C, and it is easy to predict that the electronic transition state will change if such a high-temperature hot spot acts even for an instant. It is speculated that the fine particle size and the unique electronic transition state act in combination to bring about excellent CO selectivity.

[0060] In addition, according to this manufacturing method, it is possible to precipitate metallic silver nanoparticles with high dispersion and high loading rate, and it is also possible to support silver chromate (Ag2CrO4) nanoparticles on the surface of gallium oxide particles, which support the function of the co-catalyst of the metallic silver nanoparticles. This allows carbonate ions to be present in the vicinity of the silver nanoparticles as the co-catalyst, and as a result, it is possible to effectively promote the reduction of carbon dioxide. Furthermore, according to this manufacturing method, it is possible to use a compound such as silver oxide that is not dissolved in the reaction solution in a solid state as a silver supply source, although this is not limited thereto. When a compound that is not dissolved in the reaction solution is used, the reaction solution does not contain harmful substances such as anions, and waste liquid treatment is easy.

[0061] In contrast, it is difficult to support metallic silver nanoparticles at a high dispersion and high loading rate using the impregnation method and photoelectrodeposition method proposed in the past. For example, Patent Document 1 describes that the amount of silver supported is 0.2 to 2 mass% of gallium oxide when using the photoelectrodeposition method and 0.05 to 2% when using the impregnation method, and that if the amount is more than the optimal range, the particle size of the silver nanoparticles becomes large, losing effects such as catalytic activity, or reducing the surface active sites of gallium oxide (Patent Document 1,

[0014] and

[0015] ).

[0062] In addition, the impregnation method and photoelectrodeposition method proposed in Patent Document 1 use a precursor solution such as an aqueous solution in which silver nitrate is dissolved. Anions such as nitrate ions contained in such precursor solutions are harmful substances that cause air pollution. Therefore, the impregnation method and photoelectrodeposition method require waste liquid treatment to detoxify the harmful substances. However, the manufacturing method of this embodiment does not exclude the use of compounds that dissolve in the reaction solution. Even in such a case, the effect of precipitating metallic silver nanoparticles with high dispersion and high loading rate can be obtained.

[0063] Furthermore, in the manufacturing method proposed in Patent Document 2, ultrasonic treatment is performed only to disperse the precious metal oxide, and the precious metal oxide is reduced in a heating step after ultrasonic treatment (Patent Document 2,

[0038] ). Therefore, it is clearly different from the method of the present embodiment in which the silver source (silver oxide, etc.) is reduced by ultrasonic treatment. In the manufacturing method of the present embodiment, it is possible to support sufficiently reduced silver nanoparticles without heating after ultrasonic treatment. EXAMPLES

[0064] The present embodiment will be described in more detail with reference to the following examples, but the present invention is not limited to the following examples.

[0065] (1) Preparation of photocatalyst particles [Example 1] Photocatalyst particles (metallic silver nanoparticle-supported gallium oxide particles) were produced by reducing silver nanoparticles using ultrasonic treatment. The silver concentration (supported amount) relative to gallium oxide was set to 3.0 mass%. Specifically, the sample was produced as follows.

[0066] <Preparation process> Gallium oxide particles (Ga2O3, Kojundo Chemical Laboratory Co., Ltd.) and silver oxide (Ag2O, Fujifilm Wako Pure Chemical Co., Ltd.) were prepared. The gallium oxide particles had a purity of 99.99% and the average particle diameter was approximately 3 μm in the long axis and approximately 1 μm in the short axis. The silver oxide particles had a purity of 99% and were aggregates with a primary particle diameter of approximately 2 μm.

[0067] <Mixing process> The prepared gallium oxide particles (1 g) and silver oxide (32 mg) were added to a reducing solution (50 mL). Ethanol (Fujifilm Wako Pure Chemical Industries, Ltd.) was used as the reducing solution. This produced a reaction solution.

[0068] <Ultrasonic treatment process> The resulting reaction solution was placed in an ultrasonic device (Honda Electronics Co., Ltd., WT-100-M) and subjected to ultrasonic treatment. The ultrasonic treatment was performed with two-frequency switching oscillation at 28 kHz and 45 kHz under the condition of an output of 100 W. Also, the treatment time was changed between 0 and 3 hours. At this time, the temperature of the reaction solution was maintained at 40 °C. By this treatment, silver oxide (Ag2O) in the reaction solution was reduced to change to silver (Ag). Next, the product generated by the treatment was filtered, then washed with ethanol (10 mL), and dried in the air at 60 °C for 0.5 hour to obtain gallium oxide particles supporting silver metal nanoparticles.

[0069] <Heat treatment step> The obtained gallium oxide particles supporting silver metal nanoparticles were heat-treated in the air at 200 °C for 5 minutes.

[0070] <Cr treatment step> Cr and silver were reacted by an impregnation method to produce Ag2CrO4 to prepare photocatalyst particles. First, heat-treated gallium oxide supporting silver metal nanoparticles (1.03 g) were mixed with ultrapure water (20 mL) and an aqueous chromium(III) nitrate solution (0.14 M, 1.98 mL). At this time, the amount of Cr charged was adjusted so that Ag:Cr = 1:1 (molar ratio). Next, the obtained mixed solution was heated at 80 °C for 1 hour using a water bath. The heated mixed solution was dried in the air at 80 °C for 3 hours, and the obtained dried product was calcined at 450 °C for 2 hours. Thereby, photocatalyst particles were obtained.

[0071] [Comparative Example 1] Photocatalyst particles were prepared by Cr treatment using the photoelectrolysis method (photoelectrodeposition method). First, heat-treated gallium oxide supported with silver metal nanoparticles (1.03 g) was mixed with ultrapure water (1 L) and an aqueous chromium(III) nitrate solution (0.14 M, 1.98 mL). At this time, the amount of Cr charged was adjusted so that Ag:Cr = 1:1 (molar ratio). Next, argon (Ar) gas was blown into the obtained mixed solution for gas replacement. Then, while blowing argon gas at a flow rate of 30 mL / min, the mixed solution was irradiated with UV light for 1.5 hours using a 400 W high-pressure Hg lamp to precipitate chromium hydroxide on the gallium oxide supported with silver metal nanoparticles. The solution after light irradiation was filtered to recover the powder. The recovered powder was dried at room temperature to obtain photocatalyst particles.

[0072] [Comparative Example 2] Cr treatment was not performed. Otherwise, photocatalyst particles were obtained in the same manner as in Example 1.

[0073] (2) Evaluation of photocatalyst particles Regarding the samples obtained in Example 1, Comparative Examples 1 and 2, evaluations of various properties were performed as follows.

[0074] <X-ray diffraction (XRD)> The samples were analyzed by X-ray diffraction method to examine their crystal phases. The analysis conditions were as follows.

[0075] - X-ray diffractometer: Bruker Japan, D8 DISCOVER Vario-1 - Radiation source: CuKα1 monochromated - Tube voltage: 45 kV - Tube current: 40 mA - Scan speed: 0.3° / min - Scan range (2θ): 20~60°

[0076] <TEM / EDS analysis> The samples were observed using a transmission electron microscope (TEM; HITACHI, HF-2200). The observation was performed under the condition of a transmission electron image with an acceleration voltage of 200 kV.

[0077] <CO₂ Reduction Photocatalyst Performance> The CO₂ reduction photocatalyst performance of the sample was evaluated using the evaluation apparatus shown in Fig. 2. First, ultrapure water (1 L), NaHCO₃ (0.1 M), and photocatalyst particles (0.5 g) were mixed to prepare an evaluation solution. Next, this evaluation solution was placed in the tank of the evaluation apparatus, and while blowing carbon dioxide (CO₂) gas at a flow rate of 30 mL / min, UV light was irradiated with a 400 W high-pressure Hg lamp. The gas generated after 1 hour of irradiation was analyzed using gas chromatography (Shimadzu Corporation, GC-8A) to determine the generation rates of H₂, O₂, and CO. Then, the CO selectivity was calculated based on the following formula (1).

[0078]

Equation

[0079] (3) Evaluation Results <X-ray Diffraction (XRD)> The X-ray diffraction (XRD) patterns obtained for Example 1, Comparative Examples 1 and 2 are shown in Figs. 4(a) and (b) together with the patterns of silver (Ag) and silver chromate (Ag₂CrO₄). Ga₂O₃ was seen as the main peak in all samples, but differences were observed upon detailed analysis. Specifically, the peak of Ag₂CrO₄ could be confirmed in Example 1, while the peak of Ag₂CrO₄ was not detected in Comparative Examples 1 and 2. Also, although accurate judgment was difficult due to peak overlap, the peak of Ag was detected in Comparative Examples 1 and 2, while the peak intensity of Ag was weak in Example 1.

[0080] <TEM / EDS Observation> STEM images obtained for the samples of Example 1 and Comparative Example 1 are shown in FIGS. 5 and 6, respectively. From the TEM image of Example 1, Ga2O3 columnar particles and particles with a size of several nanometers were observed. Also, Ag, Cr, and O were detected in the particles with a size of several nanometers by EDS analysis. From this, it was found that the particles with a size of several nanometers were Ag2CrO4. On the other hand, in the TEM image of Comparative Example 1, particles with a size of several nanometers were not observed. Ag nanoparticles of about 20 nm were detected, and Cr seemed to be present on Ag.

[0081] <CO2 reduction photocatalytic performance> The CO2 reduction photocatalytic performance (gas generation rate and CO selectivity) obtained for Example 1, Comparative Example 1, and 2 is shown in Table 1. To compare the performance of the samples prepared by the impregnation method (Example 1, Comparative Example 2), the sample treated with Cr (Example 1) had a CO generation rate about 2.5 times higher, although the CO selectivity was almost the same as that of the sample without Cr treatment (Comparative Example 2). On the other hand, for the sample prepared by the photoelectrolysis method (Comparative Example 1), although the CO generation rate increased compared to the sample without Cr treatment (Comparative Example 2), the H2 generation rate also increased. Therefore, the CO selectivity significantly deteriorated.

[0082]

Table 1

Explanation of symbols

[0083] 2 Evaluation apparatus 4 Tank 6 Mercury (Hg) lamp 8 Gas inlet tube 10 Gas discharge tube 12 pH meter 14 Rubber stopper 16 Stirrer 18 Bubbling filter 20 Cooling water 22 Evaluation solution 30 CO2 gas 32 Generated gas 34 Gas chromatography

Claims

1. Gallium oxide (Ga 2 O 3 2.) Providing particles and a silver (Ag) source; adding the gallium oxide particles and the silver source to a reduction solution to prepare a reaction solution; A step of irradiating the reaction solution with ultrasonic waves to produce metallic silver-supported gallium oxide particles; and The metallic silver-loaded gallium oxide particles are subjected to a chromium (Cr) treatment, thereby forming metallic silver (Ag) nanoparticles and silver chromate (Ag) nanoparticles. 2 CrO 4 ) preparing gallium oxide particles carrying nanoparticles; In carrying out the chromium treatment, the metallic silver-supported gallium oxide particles are immersed in an aqueous solution in which a chromium (Cr) compound is dissolved to precipitate the chromium (Cr) compound on the surface of the metallic silver-supported gallium oxide particles, and then the metallic silver-supported gallium oxide particles on which the chromium (Cr) compound has been precipitated are subjected to a heat treatment. A method for producing carbon dioxide reducing photocatalyst particles.

2. The silver (Ag) source is silver oxide (Ag 2 The method of claim 1 , further comprising:

3. The method according to claim 1 or 2, wherein the reducing solution comprises an alcohol.

4. The method according to any one of claims 1 to 3, wherein the frequency of the ultrasound is 28 to 45 kHz.

5. The method according to any one of claims 1 to 4, wherein the ultrasonic irradiation is carried out for 1 to 10 hours.

6. The method according to any one of claims 1 to 5, wherein the metallic silver-supported gallium oxide particles before the chromium treatment are subjected to a heat treatment at a temperature of 100 ° C. or higher in an oxygen-containing atmosphere.

7. The method according to any one of claims 1 to 6, wherein the heat treatment is carried out at a temperature of 400 to 700°C for a period of 1 to 10 hours.

8. The method according to any one of claims 1 to 7, wherein the metallic silver (Ag) nanoparticles have an average particle size of 10.0 to 50.0 nm.

9. The silver chromate (Ag 2 CrO 4 9. The method according to claim 1, wherein the nanoparticles have an average particle size of 1.0 to 30.0 nm.

10. The method according to any one of claims 1 to 9, wherein the amount of the silver component supported is 0.3 to 10.0% by mass in terms of metallic silver relative to the gallium oxide particles.

11. CO 2 The method according to any one of claims 1 to 10, wherein the photocatalyst particles have a CO selectivity of 30% or more in a reduction photocatalyst performance evaluation test. However, the CO 2 The reduction photocatalytic performance evaluation test was performed using ultrapure water (1 L), NaHCO 3 (0.1M) and the carbon dioxide reducing photocatalyst particles (0.5 g) were mixed to prepare an evaluation solution, which was then placed in the tank of the evaluation device. Then, carbon dioxide (CO 2 ) gas was blown in at a flow rate of 30 mL / min, while UV light was irradiated from a 400 W high-pressure Hg lamp. After 1 hour of irradiation, the gas generated was analyzed by gas chromatography to determine the H 2 , O 2 The CO selectivity is calculated based on the following formula (1). [0010]

Citation Information

Patent Citations

  • Silver chromate-graphene oxide composite photocatalytic material and preparation method thereof

    CN104258857A

  • Visible light responsible photocatalysis material of AgTO2 type composite oxide and its application

    CN1799690A

  • Method for manufacturing noble-metal nanomaterial

    JP2008024968A

  • Metal nanoparticle and method for producing the composite powder

    JP2010065265A

  • Method of reducing carbon dioxide

    JP2012192302A